Analysis Morphology Errors in Undergraduate Theses from the Indonesian Language and Literature Education Study Program, Pattimura University - Polibu, Julyanty Misye; Pattiasina, Petrus Jacob; Hiariej, Chrissanty (Universitas Pattimura, 2024)
Language errors are an inevitable aspect of the language acquisition process, including thesis composition, but language error analysis represents an endeavor to utilize language effectively and adhere to linguistic conventions. A frequent error in word construction pertains to morphological structure. This study aims to examine the types of morphological errors in student theses. This study included library procedures along with reading and note-taking methods for data collecting. This study identifies the following types of morphological errors: (1) omission of affixes; (2) improper application of affixes; (3) erroneous spelling of affixes frequently utilized as prepositions; (4) incorrect spelling of prepositions as affixes; (5) reduplication; (6) composition; (7) sounds that require softening. Thesis authors or students familiar with informal contexts often exhibit a deficiency in fundamental writing conventions and lack proficiency in correct spelling. Other scholars may examine the manifestations of linguistic faults in the domains of phonology or syntax within student theses.